Composition of peripheral blood immune cell compartment in stage 5 chronic kidney disease is affected by smoking and other risk factors associated with systemic inflammatory response - Zahradka, Ivan; Tichanek, Filip; Majercikova, Lucia; Duskova, Jana; Streitz, Mathias; Schlickeiser, Stephan; Osickova, Klara; Petr, Vojtech; Hruba, Petra; Reinke, Petra; Viklicky, Ondrej (Frontiers in Immunology, 2025)
BackgroundStage 5 chronic kidney disease (CKD5) is linked to complex yet not fully understood disturbances in immune system. This study aimed to investigate these disturbances by exploring the detailed composition of peripheral blood immune cell compartments in CKD5 patients and to provide integrative, multivariable dissection of how common inflammatory risk factors shape the immune landscape.MethodsThis cross-sectional study included 107 patients with chronic kidney disease stage 5 (CKD5) and 29 healthy blood donors as controls. Peripheral blood B cells, T cells, and dendritic cells were measured using a standardized and validated flow cytometry panel. The impact of selected clinical factors on immune cell composition was initially evaluated using a robust multivariate method (PERMANOVA). Variables that significantly affected immune cell composition were then included in a subsequent series of Poisson regression models, assessing predictors influence on the counts of individual immune cell subpopulations.ResultsCompared to healthy controls, CKD5 patients presented with B cell lymphopenia across all measured subsets except for plasmablasts, T cell lymphopenia with an immunosenescent phenotype predominantly in the CD4+ compartment, and significantly higher counts of LIN-HLA-DR+ antigen-presenting cells, mainly due to an increase in myeloid dendritic cell subpopulations. PERMANOVA identified smoking, CMV seropositivity, age, dialysis treatment, and atherosclerotic cardiovascular disease as factors significantly influencing peripheral blood immune composition. Subsequent Poisson regression models revealed that smoking was associated mainly with an increase in switched memory B cells, CMV seropositivity with an increase in CD4+ and CD8+ TEMRA cells, age with a decrease in naive CD8+ T cells, and dialysis treatment with an increase in marginal-zone B cells.ConclusionsPatients with CKD5 exhibit distinct composition of peripheral blood immune cells, further modified by other factors associated with systemic inflammatory response. These factors should be considered in immunomonitoring protocols and may enhance prediction of clinical outcomes such as vaccine responses.